Mobile Learning Application for Malaysia History using Virtual Reality Approach - Syafiqah, Amirah; Ismail, Azizan (Applied Information Technology And Computer Science, 2022)
Virtual reality technology is a new technology that has great potential to be widely used in education with the concept of mobile learning (M-Learning) in any subject such as History and the combination of Virtual Reality in the learning content is able to attract students’ interest in History’s subject as nowadays History is one of subject that not every student took interest. The aim of this project is to design Malaysian History Education Apps using Virtual Reality approach with syllabus from Form 5 in interactive way. This application uses First-Person Controller which is controlled from a first-person perspective and consists modules and quizTEXT